Scientific Opinion on Epizootic Hemorrhagic Disease - EFSA Panel on Animal Health and Welfare (AHAW) (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Animal Health and Welfare was asked to deliver a scientific opinion on Epizootic Hemorrhagic Disease (EHD). The disease has never been reported in the European Union, however in recent years outbreaks of disease caused by EHD Virus (EHDV) serotype 6 and 7, previously considered to be non‐pathogenic were observed in EU neighbouring countries. Clinical signs in cattle are similar to those exhibited by bluetongue affected animals and production losses may be significant. Sheep, although susceptible to infection, do not present clinical signs. EHDV is transmitted between its ruminant hosts by species of Culicoides biting midges. There is no scientific evidence to suggest that mosquitoes have a role in the transmission of EHDV. In Europe several suspected EHDV vectors are present, including C. imicola and vectors within the Pulicaris and Obsoletus complex. An assessment of the risk of introduction of EHD virus into the EU was developed by considering 3 possible entrance pathways: i) via imported infectious animals ii) via infectious vectors and iii) other routes e.g. via vaccines or germplasm. The risk estimate for the introduction varied according to the pathway considered and the season of introduction. Vector abundance and climatic conditions could be favourable to sustain EHDV circulation; therefore, the AHAW panel concluded that presence of EHDV in neighbouring countries poses a significant risk for introduction and establishment of EHDV in the EU. A surveillance programme (active and passive) in high risk areas using sensitive diagnostic tests should be established for early detection of disease introduction. In case of an outbreak of EHD in the EU, key actions should include detection of infected animals, epidemiological investigations, restriction of movements and eventually long term surveillance.